If the area of a triangle is 36 5/6 feet and the base of the triangle is 6 1/2 feet, what is the height?

Guest Jun 17, 2015

#2**+5 **### h = 11 1/3 ft

If the area of a triangle is 36 5/6 feet and the base of the triangle is 6 1/2 feet, what is the height?

A = 36 5/6 ft^{2}, base (b) = 6 1/2 height (h) = ?

$${\mathtt{h}} = {\frac{{\mathtt{2}}{\mathtt{\,\times\,}}\left({\mathtt{36}}{\mathtt{\,\small\textbf+\,}}{\frac{{\mathtt{5}}}{{\mathtt{6}}}}\right)}{\left({\mathtt{6}}{\mathtt{\,\small\textbf+\,}}{\frac{{\mathtt{1}}}{{\mathtt{2}}}}\right)}}$$

$${\mathtt{h}} = {\frac{\left({\mathtt{73}}{\mathtt{\,\small\textbf+\,}}{\frac{{\mathtt{2}}}{{\mathtt{3}}}}\right)}{\left({\mathtt{6}}{\mathtt{\,\small\textbf+\,}}{\frac{{\mathtt{1}}}{{\mathtt{2}}}}\right)}}$$

$${\mathtt{h}} = {\frac{\left({\frac{{\mathtt{442}}}{{\mathtt{6}}}}\right)}{\left({\frac{{\mathtt{39}}}{{\mathtt{6}}}}\right)}}$$

$${\mathtt{h}} = {\frac{{\mathtt{2\,652}}}{{\mathtt{234}}}} \Rightarrow {\mathtt{h}} = {\mathtt{11.333\: \!333\: \!333\: \!333\: \!333\: \!3}}$$

Guest Jun 18, 2015

#1**+5 **

A = (1/2)bh ... so.....

36 + 5/6 = (1/2)(6 + 1/2) h and 36 + 5/6 = 221/6 and 6 + 1/2 = 13/2 ...so.....

221/6 = (1/2)(13/2) h

221/6 = (13/4) h multiply both sides by 4/13

(221/6)(4/13) = h

(221/13)(4/6) = h

(221/13)(2/3) = 442 / 39 = 34/3 ft = h = (11 + 1/3) ft

CPhill
Jun 17, 2015

#2**+5 **

Best Answer### h = 11 1/3 ft

If the area of a triangle is 36 5/6 feet and the base of the triangle is 6 1/2 feet, what is the height?

A = 36 5/6 ft^{2}, base (b) = 6 1/2 height (h) = ?

$${\mathtt{h}} = {\frac{{\mathtt{2}}{\mathtt{\,\times\,}}\left({\mathtt{36}}{\mathtt{\,\small\textbf+\,}}{\frac{{\mathtt{5}}}{{\mathtt{6}}}}\right)}{\left({\mathtt{6}}{\mathtt{\,\small\textbf+\,}}{\frac{{\mathtt{1}}}{{\mathtt{2}}}}\right)}}$$

$${\mathtt{h}} = {\frac{\left({\mathtt{73}}{\mathtt{\,\small\textbf+\,}}{\frac{{\mathtt{2}}}{{\mathtt{3}}}}\right)}{\left({\mathtt{6}}{\mathtt{\,\small\textbf+\,}}{\frac{{\mathtt{1}}}{{\mathtt{2}}}}\right)}}$$

$${\mathtt{h}} = {\frac{\left({\frac{{\mathtt{442}}}{{\mathtt{6}}}}\right)}{\left({\frac{{\mathtt{39}}}{{\mathtt{6}}}}\right)}}$$

$${\mathtt{h}} = {\frac{{\mathtt{2\,652}}}{{\mathtt{234}}}} \Rightarrow {\mathtt{h}} = {\mathtt{11.333\: \!333\: \!333\: \!333\: \!333\: \!3}}$$

Guest Jun 18, 2015